Considering data literacy using Kuhlthau's Information Search Process: Implications for librarians and data providers. Issue 3 (18th November 2020) - Jefferson, Charissa Odelia; Stierholz, Katrina; Fontichiaro, Kristin; Hoelter, Lynette
Abstract: This article uses Kuhlthau's Information Search Process (ISP) to illustrate ways that librarians can assist students and collaborate with data providers to improve the data search process. Librarians and data providers share similar data literacy goals, and this paper pools the expertise of both groups to focus on strategies and interventions that support novice researchers. We explore our combined experiences and jointly step through students' research phases to examine how each group can contribute to improving that experience. We review students' data literacy needs throughout the research process through the lens of Kuhlthau's six-stage, iterative ISP. Kuhlthau's framework, rooted in empathy, maps to existing knowledge about what students do, think, and feel at various stages of the search process. We identify "zones of intervention" that are both consistent with Kuhlthau's research and are novel to data-rich research projects.